Left ventricular beat to beat performance in atrial fibrillation: dependence on contractility, preload, and afterload - Muntinga, H (1999)
OBJECTIVE—To assess independent determinants of beat to beat variation in left ventricular performance during atrial fibrillation. DESIGN—Prospective study. SETTING—University hospital. PATIENTS—Seven patients with chronic non-valvar atrial fibrillation. INTERVENTIONS—Invasive and non-invasive haemodynamic variables were assessed using a non-imaging computerised nuclear probe, a balloon tipped flow directed catheter, and a non-invasive fingertip blood pressure measurement system linked to a personal computer. MAIN OUTCOME MEASURES—Left ventricular ejection fraction, left ventricular volume, ventricular cycle length, pulmonary capillary wedge pressure, and measures of left ventricular afterload (end systolic pressure/stroke volume) and contractility (end systolic pressure/end systolic volume) were calculated on a beat to beat basis during 500 consecutive RR intervals. A statistical model of the beat to beat variation of the ejection fraction containing these variables was constructed by multiple regression analysis. RESULTS—Positive independent relations with ejection fraction were found for preceding RR interval, contractility, and end diastolic volume, while inverse relations were found for afterload, preceding end systolic volume, and preceding contractility (all variables, p < 0.0001). A relatively strong interaction was found between end diastolic volume and afterload, indicating that ejection fraction was relatively more enhanced by preload in the presence of low afterload. CONCLUSIONS—The varying left ventricular systolic performance during atrial fibrillation is independently influenced by beat to beat variation in cycle length, preload, afterload, and contractility. Beat to beat variation in preload shows its effect on ventricular performance mainly in the presence of a low afterload.   Keywords: atrial fibrillation; contractility; haemodynamic variables